2020
DOI: 10.1101/2020.02.28.20029173
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Analysis on the Clinical Characteristics of 36 Cases of Novel Coronavirus Pneumonia in Kunming

Abstract: Objective: To analyze the clinical characteristics of patients with novel coronavirus pneumonia in Kunming City, and to study the correlation between nutritional status and immune function. Methods: Clinical data of 36 patients with novel coronavirus pneumonia in isolation area of Kunming Third People's Hospital from January 31 to February 15, 2020 were collected, and the basic situation, clinical characteristics, laboratory examination and CT imaging characteristics were analyzed. Serum albumin (ALB), prealbu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 4 publications
0
5
0
1
Order By: Relevance
“…Among the 16 observational studies,[ 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 ] 12 were performed at a single center and 4 were multicenter studies. The sample sizes ranged widely across studies (median 90 patients; range 24 to 416 patients).…”
Section: Resultsmentioning
confidence: 99%
“…Among the 16 observational studies,[ 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 ] 12 were performed at a single center and 4 were multicenter studies. The sample sizes ranged widely across studies (median 90 patients; range 24 to 416 patients).…”
Section: Resultsmentioning
confidence: 99%
“…A total of 43 studies including 10,676 COVID-19 patients (confirmed by laboratory real-time reverse transcription polymerase chain reaction [RT-PCR] testing) were included in the overall analysis. [20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35]37,38,41,42,45,47,[49][50][51][52][53][54][55]58,59,[62][63][64][65][66][67][68][69][70][71]73,76 The pooled prevalence of diarrhea symptoms across these studies was 7.7% (95% CI, 7.2%-8.2%). When analyzing by country (studies from China vs studies from other countries), the pooled prevalence of diarrhea in studies from countries other than China was much higher at 18.3% (95% CI, 16.6%-20.1%).…”
Section: What Are the Gastrointestinal Manifestations Of Covid-19?mentioning
confidence: 99%
“…In hospitalized patients, across 39 studies including 8,521 patients, the pooled prevalence was slightly higher at 10.4% (95% CI, 9.4%-10.7%) compared with outpatients. [20][21][22][23][25][26][27][28]30,[33][34][35]38,41,42,[44][45][46][49][50][51][52][53][54][55]60,[62][63][64][65][66][67][68][70][71][72][73][74]76 In 3 studies including 1701 outpatients, the pooled prevalence was 4.0% (95% CI, 3.1%-5.1%). 31,59,63 As part of the sensitivity analysis, we identified 35 studies including 9717 patients that described diarrhea, and explicitly reported that it was one of the initial presenting sympto ms. [20][21][22][23][26][...…”
Section: What Are the Gastrointestinal Manifestations Of Covid-19?mentioning
confidence: 99%
See 1 more Smart Citation
“…Among the 20 research articles included in the analysis, fever was found to be a dominant symptom in most of the articles [9,[11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29] (Fig. 1) as main stress was given on flulike symptoms except for one study in which fever onset was absent and gastrointestinal symptoms were the initial presentation in coronavirus infected pneumonia patients [26].…”
Section: Resultsmentioning
confidence: 99%